Effects of N-Glycosylation on the Structure, Function, and Stability of a Plant-Made Fc-Fusion Anthrax Decoy Protein - Xiong, Yongao; Karuppanan, Kalimuthu; Bernardi, Austen; Li, Qiongyu; Kommineni, Vally; Dandekar, Abhaya M.; Lebrilla, Carlito B.; Faller, Roland; McDonald, Karen A.; Nandi, Somen (Frontiers in Plant Science, 2019)
Protein N-glycosylation is an important post-translational modification and has influences on variety of biological processes at cellular and molecular level, making glycosylation a major study aspect for glycoprotein based therapeutics. To achieve a comprehensive understanding on how N-glycosylation impacts on protein properties, a Fc-fusion anthrax decoy protein, viz rCMG2-Fc, was expressed in Nicotiana benthamiana plant with three types of N-glycosylation profiles. Those profiles included plant complex-type (APO or GnGnXFAPO), oligomannose-type (ER or MAN8ER) and aglycosylated (Agly). The decoy protein binds to the protective antigen (PA) of anthrax through its CMG2 domain and inhibits toxin endocytosis. The protein expression, sequence, N-glycosylation profile, binding kinetics to PA, toxin neutralization efficiency, and thermostability were determined experimentally. In parallel, we performed molecular dynamics (MD) simulations of the predominant full-length rCMG2-Fc glycoform for each of the three N-glycosylation profiles to understand the effects of glycosylation at the molecular level. Glycosylation showed strong stabilizing effects on rCMG2-Fc during in planta accumulation, evidenced by the over 2-fold higher expression and less protein degradation observed for glycosylated variants compared to the Agly variant. Protein function was confirmed by toxin neutralization assay (TNA), with effective concentration (EC50) rankings from low to high of 67.6 ng/mL (APO), 83.15 ng/mL (Agly) and 128.9 ng/mL (ER). The binding kinetics between rCMG2-Fc and PA were measured with bio-layer interferometry (BLI), giving sub-nano molar affinities regardless of protein glycosylation and temperatures (25°C and 37°C). The protein thermostability was examined utilizing the PA binding ELISA, aiming to provide information on EC50 differences, where the fraction of functional ER variant decayed after overnight incubation at 37°C, and no significant change was observed for APO or Agly variants. In MD simulations, the MAN8ER glycoform shows quantitatively higher distance between the CMG2 and Fc domains, as well as higher hydrophobic solvent accessible surface areas (SASA), indicating a possibly higher aggregation tendency of the ER variant. This study highlights the impacts of N-glycosylation on protein properties and provides insight into the effects of glycosylation on protein molecular dynamics.